Lower limb joint kinetics in the starting blocks and first stance in athletic sprinting. Issue 16 (18th August 2017) - Brazil, Adam; Exell, Timothy; Wilson, Cassie; Willwacher, Steffen; Bezodis, Ian; Irwin, Gareth
ABSTRACT: The aim of this study was to examine lower limb joint kinetics during the block and first stance phases in athletic sprinting. Ten male sprinters (100 m PB, 10.50 ± 0.27 s) performed maximal sprint starts from blocks. External force (1000 Hz) and three-dimensional kinematics (250 Hz) were recorded in both the block (utilising instrumented starting blocks) and subsequent first stance phases. Ankle, knee and hip resultant joint moment, power and work were calculated at the rear and front leg during the block phase and during first stance using inverse dynamics. Significantly ( P < 0.05) greater peak moment, power and work were evident at the knee joint in the front block and during stance compared with the rear block. Ankle joint kinetic data significantly increased during stance compared with the front and rear block. The hip joint dominated leg extensor energy generation in the block phase (rear leg, 61 ± 10%; front leg, 64 ± 8%) but significantly reduced during stance (32 ± 9%), where the ankle contributed most (42 ± 6%). The current study provides novel insight into sprint start biomechanics and the contribution of the lower limb joints towards leg extensor energy generation.